Rationales and Advantages of Financing Infrastructure Through Public – Private Partnerships : A Systematic Literature Review - Malik, Sakshi; Kaur, Simrit (Indian Journal of Finance, 2021)
The procurement of infrastructure is a significant concern for developed and developing countries alike. To address the challenges of infrastructure provision, several countries are exploring the possibility of procuring infrastructure through public–private partnerships (PPPs). Against this background, the current study had a primary research objective of identifying the rationale and factors that support the implementation of PPPs as a means to build infrastructure. Further, the study also aimed to discuss the benefits associated with the PPP modality of procuring infrastructure. For this purpose, the present study relied on a comprehensive review of existing studies using systematic literature review method. Based on qualitative analysis of articles published during 2006 – 2020 using Quirkos software, the following four key rationales supporting the implementation of PPPs were identified: low quality of existing infrastructure, widening infrastructure deficits, market and non-market failures, and budgetary constraints of the governments. Further, the results highlighted that PPPs provide several benefits, including access to financial resources and expertise of the private sector, better risk allocation, efficiency gains, enhancement or value for money, cost-effectiveness, reliability, and timely infrastructure development.